SYNCRETISM OF THE SEASONAL RITUALS IN THE LATGALIAN BORDERLAND - Dukaļska, Iveta (Via Latgalica, 2010)
German written sources are representing information on masquerade traditions in Latvia already in the 17th century - Latvian mask parades in 1636 are described by the Kurzeme and Zemgale Superintendent, P. Einhorn. (Jansons 2010: 49). Information about the Latvian masquerade traditions from the Christian Church sources in the nineteenth century and at the beginning of the twentieth century have been negative, which is analyzed in 30-ties of the 20th century by ethnologist Jānis Alberts Jansons in his work "The Latvian mask parades”, but through a field study at the beginning of 21st century conclusion can be drawn that these traditions have been explicitly significant within the rural cultural environment up to 60-70-ies of the 20th century. Research of traditions does not lose its importance also in today's multicultural society, as it helps to understand the human philosophy of life and relationship with nature of the rural cultural environment.This article aims to describe the two Christmas masquerade traditions ‘īšonu gradzēs’ and ‘идти коледовать’ (‘īt kaladnīkūs’– to go mummery), where in Latvia, as elsewhere in the world, "mask parades are associated with celebrations and public holidays” (Rancāne 2008: 217). The paper is also dealing with two Easter traditions – ‘ходить по алелуя’ (walk alelujah), and ‘īt laluoti’ in several aspects related to the Christian church traditions, but inheritance of them has been performed in family, by transfer of the knowledge and skills from generation to generation. In course of the research attention focuses on origin, rites and social sense of the tradition: ‘īšona gradzēs, идти коледовать, ходить по алелуя’ and ‘īt laluoti’. Similarities and dissimilarities are revealed in ritual processes of the said traditions.Research hypothesis: upon analysis of winter and spring cycle anniversary celebration rituals of the ethnic groups residing in Latgale, it is possible to discover features of syncretism of these traditions. Features of syncretism of the traditions become apparent in two ways. First, through interaction between the Christian church and folk traditions, which is characterized by: adjustment of the ritual traditions to calendar of the Christian Church holidays, not the natural cycle of solstice; music repertoire, where the narrators do not distinguish between folk songs and the chants, calling then God's songs, and functionality, where the performers of rituals, as narrators indicate, are the first carriers of Christ's message.Second, syncretism emerges in traditions of various ethnic groups, affected both by ethnic groups living in the Latgale borderland, the cultural environment developed by them and usage of languages. as well as interaction between the lyrics and musical repertoire and personal experience, grounded on the tradition inherited in the family.The study is based on materials of the Latvian Folklore Depository and field research interviews conducted by author of the article in Ludza 2005-2008 (currently Ludza, Kārsava, Cibla, Krāslava and Zilupe municipalities), which covers informatively dense time period: 30-70-ties of the 20th century. The comparative method is used for analysis, where information derived in the field studies is compared to materials from published sources and literature with regard to the rituals of Christmas masquerade tradition and Easter tradition. Theoretical basis of research comprises publications of Latvian (Jānis Alberts Jansons, Aīda Rancāne, Anda Beitāne, etc.) and Polish ethnomusicologist (Gustav Juzala) and other folklore specialists.Expressions of syncretism in seasonal rituals in the Latgale borderland are not specifically studied, therefore the author's research is considered to be innovative, but it is not completed and represents only early stages of more serious study.